2016
DOI: 10.1186/s12942-016-0037-9
|View full text |Cite
|
Sign up to set email alerts
|

Using a geographic information system to enhance patient access to point-of-care diagnostics in a limited-resource setting

Abstract: BackgroundRapid and accurate diagnosis drives evidence-based care in health. Point-of-care testing (POCT) aids diagnosis by bringing advanced technologies closer to patients. Health small-world networks are constrained by natural connectivity in the interactions between geography of resources and social forces. Using a geographic information system (GIS) we can understand how populations utilize their health networks, visualize their inefficiencies, and compare alternatives.MethodsThis project focuses on cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 20 publications
1
34
0
Order By: Relevance
“…Searches using IEEE Xplore did not yield additional relevant articles. In the interests of brevity, the reader can find detailed discussions of geospatial theory, software apps, and analytical techniques in Ferguson et al (28)(29)(30). Visual logistics illustrate several key concepts.…”
Section: Methods and Scope Methodsmentioning
confidence: 99%
“…Searches using IEEE Xplore did not yield additional relevant articles. In the interests of brevity, the reader can find detailed discussions of geospatial theory, software apps, and analytical techniques in Ferguson et al (28)(29)(30). Visual logistics illustrate several key concepts.…”
Section: Methods and Scope Methodsmentioning
confidence: 99%
“…Although OpenStreetMap data have been used in other studies in which these data were confirmed as an accurate representation of what's on the ground Generating framework GIS data in data-poor settings 325 (Ferguson et al 2016), this was not the case for our study area, as illustrated by the huge data gaps in Figure 3. At the time of writing this paper, arrangements are underway to publish all the new data to the OpenStreetMap platform to serve as a contribution to a wider GIS audience needing access to data in the study area.…”
Section: Global Flood Observatorymentioning
confidence: 79%
“…Using GIS to inform the implementation of health services has been shown to be useful [42][43][44]. GIS effectively enables the implementation of POC testing in health networks to streamline decision making at the POC [45]. Geospatial science has also been proven to be useful in creating solutions for population access to POC testing during emergencies, outbreaks, and disasters such as the present COVID-19 pandemic [46].…”
Section: Discussionmentioning
confidence: 99%
“…Geospatial science has also been proven to be useful in creating solutions for population access to POC testing during emergencies, outbreaks, and disasters such as the present COVID-19 pandemic [46]. Hence, GIS helps improve patient outcomes, time and money, ensure that the health networks are sufficiently resourced to deliver needed health services to the population [45]. Despite these strengths, there are several limitations worth noting such as our inability to include non-spatial factors in the analysis.…”
Section: Discussionmentioning
confidence: 99%